Eletrodeposição conjunta de zinco-níquel. - Silva, Gecílio Pereira da (1996)
The present work describes the synthesis, the characterization, the influence of some parameters in the process and the chamber corrosion studied on Zn-Ni alloys. The codeposits were obtained by electrodeposition on the carbon steel surfaces with circular shape, from conventional alkaline cyanide solutions, used for zinc coatings, modified by the addition of nickel chloride. The analysis of alloys composition, carried out by atomic absorption spectrofotometry, shown that different composition of the Zn-Ni alloys can be obtained using this electrochemical bath in the same conditions of current, time and potential. The accelerated corrosion tests carried out in the alloys obtained from the solutions contend 1,5g/L and 3,0 g/L of Ni, shown chatodic behavior for the corrosion protection of the substrate, but in the cases of the electrodeposition make from solutions with high Ni contend, the alloys shown a anodic behavior for the protection. The study of the influence of the current on the formation of the electrodeposits shown that the total mass electrodeposited increase with the current density and, in this current range, the codeposition is normal. The anomalous electrodeposition trends to occur with the corrent density rissing. The electrochemical test carried out in the Hull cell showed that alloys, obtained from solutions with low Ni contents and in the range of 2,0 A /dm2 - 5,0 A/dm2, have homogeneous distribution of layers and a good throwing power. The structural analysis of the deposits were made using conventional optical techique and X-rays diffraction. The results showed that the alloys, obtained from the solutions with low Ni conted, have a homogeneous surface composed of nodules and islands. lt was verified that the surface show columnar aspect when the Ni concentration is higher than 7,5 g/L, but the surface return to nodular aspect for the Ni concentration higher than 10,5 g/L. The X-ray analysis shown that the all the electrodeposits are crystalline.